Influence of Bioactive Restorative Materials on Secondary Caries Prevention: A Clinical and In Vitro Study - Helal M. Sonbul (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Secondary caries remains a significant challenge in restorative dentistry, often leading to restoration failure and the need for retreatment. Bioactive restorative materials, such as bioactive glass, giomers, and calcium-silicate-based materials, have been developed to promote remineralization and inhibit bacterial growth. Materials and Methods: A total of 60 patients with Class II carious lesions were recruited for the clinical study and divided into three groups (n = 20) based on the restorative material used: bioactive glass-based composite, giomer, and conventional composite resin. The restorations were evaluated over 12 months for secondary caries development using the International Caries Detection and Assessment System II (ICDAS II) criteria and radiographic analysis. Additionally, an in vitro study was conducted using 45 extracted molars restored with the same materials, subjected to artificial caries challenge in a pH-cycling model. Microhardness and lesion depth were assessed using Vickers hardness testing and confocal laser scanning microscopy. Results: Clinically, secondary caries incidence was lowest in the bioactive glass group (10%), followed by the giomer group (15%), and highest in the conventional composite group (30%). Radiographic analysis confirmed a significant reduction in lesion progression in bioactive materials (P < 0.05). In vitro results showed that bioactive restoratives exhibited significantly higher remineralization potential, with lesion depths of 50 ± 5 μm in bioactive glass, 65 ± 7 μm in giomer, and 110 ± 8 μm in conventional composite resin (P < 0.05). Conclusion: Bioactive restorative materials demonstrate superior efficacy in preventing secondary caries compared to conventional composite resins. Their remineralization potential and antibacterial properties contribute to prolonged restoration longevity and reduced risk of recurrent decay.